ΧΡΟΝΙΚΑ ΓΙΑ ΤΗΝ ΙΣΤΟΡΙΑ ΤΗΣ ΕΛΛΗΝΙΚΗΣ ΚΟΙΝΟΤΗΤΑΣ ΒΕΝΕΤΙΑΣ (18ΟΣ ΑΙΩΝΑΣ) - ΚΟΥΤΜΑΝΗΣ ΣΩΤΗΡΗΣ (Eoa kai Esperia, 2007)
During the eighteenth century the religious-ecclesiastical crisis of theGreek community of Venice, caused by the conversion of Meletios Typaldos,the Metropolitan of Philadelphia (1685-1713), to Roman Catholicism,resulted in the production of a large number of texts regarding the history ofthe Greek presence in Venice. These writings were composed in the Italian byVenetian officers, Catholic theologians and members of the Orthodoxconfraternity of San Nicolò dei Greci. In our study we use the term"chronicles" (memorie) in order to define those various compositions(informazioni, scritture, notizie, relazioni), which were directed primarily tothe Venetian authorities and whose main subject was the religious rights of theOrthodox Greeks and the ecclesiastical jurisdiction of the Latin Patriarch ofVenice over them. Yet the problem of religious freedom was treated by theauthors as a historical issue. The interpretation and analysis of the papal andVenetian decrees involved the historical approach and engendered textualstrategies of historical representation. Very often repetitious and rhetorical,the memorie nevertheless revealed the perception, both of the Greeks and theVenetians of the 18th century, of Greek community’s past. The present paper gives abstracts of fourteen chronicles of this kind and,since the majority of them are anonymous and undated, it attempts